A 2.5d glass cover plate ag etching process
Patent Information
- Application Number
- CN202611336788.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]为了确保玻璃盖板AG蚀刻工艺的AG面粗糙度、非AG面光泽度的均匀性,避免印刷耐酸保护油墨导致边缘出现油墨溢墨而污染AG蚀刻面的问题,或者耐酸保护膜粘附不牢导致边缘容易藏酸的问题,本申请提供了一种2.5D玻璃盖板AG蚀刻工艺
1.通过在玻璃的非AG面满面印刷复合耐酸油墨形成致密复合耐酸油墨保护层,然后通过CNC去除外周的复合耐酸油墨保护层,不仅能够完整保护整个非AG面,还能够确保整个AG面均无油墨污染,既避免了覆耐酸保护膜边缘粘附不牢的问题,进而使蚀刻AG更均匀,提升了AG效果,同时不会影响非AG面光泽度的均匀性;
Smart Images

Figure CN122916448A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of material processing, and in particular to an AG etching process for 2.5D glass cover plates. Background Technology
[0002] AG (Agglomerate Reflection) processing achieves multi-angle diffuse reflection effects by specially treating one or both sides of glass. It is widely used in outdoor displays, automotive applications, mobile phones, tablets, industrial control products, and other smart devices. This reduces glare, weakens ambient light interference, and improves image clarity and color saturation. Early industry practices primarily used spray-coating AG films, but AG coatings have poor high-temperature resistance, hinder ion exchange during glass chemical strengthening, and are prone to wear and peeling. This method has been gradually abandoned by most manufacturers. Currently, the mainstream approach is chemical etching AG, which directly forms the AG microstructure on the glass substrate. The resulting AG structure is robust and wear-resistant, enjoying greater market acceptance.
[0003] Currently, the process for etching AG on 2.5D glass covers typically involves first applying a protective ink to the raw glass material, followed by cutting, CNC machining, edge polishing, and surface polishing. Afterward, the protective ink is removed and the glass is cleaned, and then an acid-resistant protective ink is printed or an acid-resistant protective film is applied. This is followed by pretreatment, frosted etching, chemical polishing, and finally, another cleaning. This process is widely used in the industry to solve the AG etching problem of 2.5D glass covers.
[0004] However, existing 2.5D glass cover etching (AG) technology still has some obvious drawbacks. After CNC machining and polishing, the entire surface is printed with acid-resistant protective ink, which can lead to ink overflow at the edges, contaminating the AG etched surface. Furthermore, the edges are prone to shrinkage and lifting, resulting in uneven AG etching and ultimately poor AG quality. On the other hand, the acid-resistant protective film is prone to poor adhesion at the edges, easily trapping acid. This can cause corrosion marks on the non-AG surfaces of the product after AG etching and chemical polishing, affecting the uniformity of gloss on the non-AG surfaces. Summary of the Invention
[0005] To ensure the uniformity of AG surface roughness and non-AG surface gloss in the AG etching process of glass cover plates, and to avoid the problem of ink overflow at the edges contaminating the AG etched surface due to printing acid-resistant protective ink, or the problem of acid easily trapped at the edges due to poor adhesion of the acid-resistant protective film, this application provides a 2.5D glass cover plate AG etching process.
[0006] A 2.5D glass cover AG etching process includes the following steps: S1: Cleaning is performed after laser cutting of the glass raw material; S2: Print composite acid-resistant ink on the non-AG side of the glass, and form a dense composite acid-resistant ink protective layer after baking and curing. S3: CNC machining is performed on the glass printed with a composite acid-resistant ink protective layer to obtain a glass semi-finished product with a 2.5D profile; S4: Physically polish the edges and 2.5D curved surfaces of the glass semi-finished product; S5: The polished glass semi-finished product is cleaned in sequence with acidic detergent, weak alkaline detergent and pure water; S6: After the glass semi-finished product is hung and fixed, it is immersed in AG etching solution for etching treatment and then cleaned. S7: The etched glass semi-finished product is immersed in polishing liquid for chemical polishing treatment and then cleaned. S8: Immerse the glass semi-finished product in a deinking agent to remove the ink, and then clean it to obtain the finished product.
[0007] By adopting the above technical solution, the process of first printing acid-resistant protective ink and then performing CNC machining to remove the peripheral ink not only completely protects the entire non-AG surface but also ensures that the entire AG surface is free of ink contamination. The use of a printing-curing method to obtain a dense composite acid-resistant ink protective layer improves the adhesion between the composite acid-resistant ink protective layer and the non-AG glass surface, as well as the cohesive force of the ink layer itself. This allows it to better resist mechanical shearing friction and prevents cracking and wear of the dense composite acid-resistant ink protective layer during CNC machining, physical polishing, and other mechanical operations. Furthermore, this... The composite acid-resistant ink protective layer applied for exhibits good thermal stability and chemical inertness under the high-temperature environments of subsequent CNC machining, physical polishing, etching, and chemical polishing. Therefore, the ink maintains stable performance during processing, especially in the high-temperature scenarios of CNC machining. The heat distortion temperature of the dense composite acid-resistant ink protective layer can be increased to over 210℃, and the high-temperature shrinkage rate is controlled within 1%, effectively avoiding problems such as softening shrinkage, edge curling, and delamination of the dense composite acid-resistant ink protective layer. This allows the dense composite acid-resistant ink protective layer to completely protect the entire non-AG surface during AG etching. This process achieves double-sided process compatibility, forming a protective layer by printing composite acid-resistant ink on the non-AG surface of the glass. While protecting the non-AG surface from the influence of etching and polishing solutions, it does not interfere with the etching effect of the AG surface, ultimately resulting in a 2.5D glass cover plate with uniform AG effect and good gloss uniformity on the non-AG surface.
[0008] Preferably, the composite acid-resistant ink comprises the following raw materials in parts by weight: 40-60 parts epoxy resin, 20-30 parts acrylic resin, 8-12 parts barium sulfate, 4-8 parts silica, 3-6 parts ultrafine carbon black, 5-10 parts modified cycloaliphatic amine curing agent, 15-25 parts propylene glycol methyl ether acetate, 1-3 parts leveling agent, and 1-3 parts defoamer.
[0009] By adopting the above technical solution, a highly dense film-forming matrix is constructed by compounding epoxy resin and acrylic resin. Combined with a multi-layer inorganic barrier framework formed by barium sulfate, silica, and ultrafine silica, the ink layer remains free of pinholes, swelling, and peeling throughout the 15-40 minute AG frosting etching and subsequent chemical polishing in a strongly acidic hydrofluoric acid environment. This completely isolates the etching solution from contact with the non-AG surface of the glass, thoroughly avoiding the problems of accidental corrosion and edge erosion on non-processed surfaces, and significantly improving the etching yield of 2.5D glass cover plates. In addition, ultrafine silica can form a uniformly dispersed nanoscale cross-linked support structure within the resin system, raising the heat distortion temperature of the ink to above 210℃. Under the subsequent baking and curing conditions of 150-170℃, the high-temperature volume shrinkage rate can be controlled within 1%, without problems such as softening, curling, or local delamination.
[0010] Preferably, the thickness of the composite acid-resistant ink protective layer is 15-30 μm.
[0011] By adopting the above technical solution, the thickness of the composite acid-resistant ink protective layer is controlled at 15-30μm, which can effectively protect the non-AG surface of the glass and prevent the non-AG surface from being corroded by the etching solution during the etching process; at the same time, it ensures the firmness of the ink protective layer, prevents cracks and wear during CNC machining, and is conducive to more uniform etching of AG and improves the AG effect.
[0012] Preferably, the baking and curing parameters in step S2 are: first pre-baking at a low temperature of 80℃-100℃ for 15-20 minutes, and then curing at a high temperature of 150-170℃ for 30-40 minutes.
[0013] By adopting the above technical solution, pre-baking at a low temperature of 80℃-100℃ for 15-20 minutes can initially cure the composite acid-resistant ink and reduce defects caused by excessive solvent evaporation; then, heating to a high temperature of 150-170℃ for 30-40 minutes can fully cure the composite acid-resistant ink and ensure the strength and acid resistance of the composite acid-resistant ink protective layer.
[0014] Preferably, in S6, a vacuum suction cup hanger is used to attach and fix the composite acid-resistant ink protective layer of the glass semi-finished product to one side, and the hanger does not contact the AG etched surface of the glass semi-finished product.
[0015] By adopting the above technical solution, the composite acid-resistant ink protective layer of the glass semi-finished product is adsorbed and fixed by the vacuum suction cup hanger, so that the hanger does not contact the AG etching surface of the glass semi-finished product, avoiding contamination or damage to the AG etching surface and edges by the hanger, and ensuring the uniformity and stability of the AG etching effect.
[0016] Preferably, step S4 includes the following steps in sequence: S41: Use a circumferential polishing machine or a top polishing machine to polish the edges of the glass semi-finished products. During polishing, the glass semi-finished products are stacked back to back in a string. S42: Use a flip polishing machine to polish the 2.5D curved surface of the glass semi-finished product.
[0017] By adopting the above technical solutions, such as using a back-to-back stacking of a weekly or top-mounted polishing machine to polish the edges of the glass semi-finished product and using a flip polishing machine to polish the 2.5D curved surface, the polishing effect of the edges and 2.5D curved surface of the glass semi-finished product can be effectively improved. At the same time, the composite acid-resistant ink protective layer can be avoided from being damaged, thus avoiding affecting the gloss of the non-AG surface in the future.
[0018] Preferably, the acidic detergent in step S5 is a mixed aqueous solution of hydrofluoric acid and citric acid with a mass concentration of 2-5%; the weakly alkaline detergent is a mixed aqueous solution of sodium carbonate and sodium dodecylbenzenesulfonate with a mass concentration of 0.5-2% and a pH ≤ 12.
[0019] By adopting the above technical solution, an acidic detergent consisting of a mixed aqueous solution of hydrofluoric acid and citric acid with a mass concentration of 2-5% is used to remove polishing powder residue from the product surface. Then, a weakly alkaline detergent consisting of a mixed aqueous solution of sodium carbonate and sodium dodecylbenzene sulfonate with a mass concentration of 0.5-2% and a pH ≤ 12 is used to clean the surface. This ensures cleanliness while preventing damage and peeling of the composite acid-resistant ink protective layer. Finally, the residual acidic and weakly alkaline detergents are washed away with pure water.
[0020] Preferably, the AG etching solution comprises the following raw materials in parts by weight: 20-30 parts hydrofluoric acid, 10-15 parts sulfuric acid, 8-12 parts ammonium fluoride, 0.5-2 parts surfactant, and 40-50 parts deionized water.
[0021] By adopting the above technical solution, AG etching of 2.5D glass cover plates can be performed more stably and effectively, avoiding problems such as ink overflow of acid-resistant protective ink printed all over the surface and poor adhesion of acid-resistant protective film at the edges in the existing technology, thus obtaining a uniform and good AG etching effect and ensuring uniform gloss on the non-AG surface of the product.
[0022] Preferably, the polishing liquid comprises the following raw materials in parts by weight: 10-15 parts hydrofluoric acid, 5-8 parts hydrochloric acid, 3-5 parts glycerol, and 70-80 parts deionized water.
[0023] By adopting the above technical solutions, good chemical polishing results can be achieved, promoting the efficient and stable operation of the overall process.
[0024] Preferably, the deinking agent is an alkaline deinking agent composed of sodium hydroxide and sodium silicate at a mass concentration of 5-8%.
[0025] By adopting the above technical solution, the ink can be effectively removed without causing excessive corrosion to the glass, and a high-quality 2.5D glass cover plate can be obtained.
[0026] In summary, this application includes at least one of the following beneficial technical effects: 1. By printing a dense composite acid-resistant ink protective layer on the entire non-AG surface of the glass, and then removing the outer periphery of the composite acid-resistant ink protective layer by CNC, not only can the entire non-AG surface be completely protected, but also the entire AG surface can be ensured to be free of ink contamination. This avoids the problem of poor adhesion at the edges of the acid-resistant protective film, thereby making the AG etching more uniform and improving the AG effect, while not affecting the uniformity of the gloss of the non-AG surface. 2. The composite acid-resistant ink protective layer has good thermal stability and chemical inertness in high-temperature environments. Therefore, the ink can maintain stable performance during processing. Especially in high-temperature scenarios of CNC machining, the heat distortion temperature of the dense composite acid-resistant ink protective layer can be increased to above 210℃, and the high-temperature shrinkage rate is controlled within 1%, which effectively avoids the problems of softening shrinkage, curling and delamination of the dense composite acid-resistant ink protective layer. 3. It improves the adhesion between the composite acid-resistant ink protective layer and the non-AG glass surface, as well as the cohesive force of the ink layer itself. It can better resist mechanical shear friction and avoid cracking and wear of the dense composite acid-resistant ink protective layer during mechanical operations such as CNC machining and physical polishing. Attached Figure Description
[0027] Figure 1 This is a flowchart of an AG etching process for a 2.5D glass cover plate according to this application. Detailed Implementation
[0028] The following examples illustrate this. Figure 1 This application will be described in further detail. Example
[0029] The ingredients are as follows: Bisphenol A type epoxy resin, manufacturer: Jiangsu Sanmu Chemical Co., Ltd., CAS: 61788-97-4; Acrylic resin, manufacturer: Guangdong Tongbu Chemical Co., Ltd., CAS: 25036-15-1; Modified cycloaliphatic amine curing agent, manufacturer: Jiangsu Changzhou Runyou Chemical Co., Ltd., CAS: 176716-84-8; Barium sulfate, manufacturer: Guangdong Yuanlei Powder Co., Ltd., CAS: 7727-43-7; Fumed silica, manufacturer: Guangzhou Jibisheng Technology Industry Co., Ltd., CAS: 112945-52-5; Ultrafine silica, manufacturer: Zhuzhou Xinglong New Material Co., Ltd., CAS: 10279-57-9; Propylene glycol methyl ether acetate, manufacturer: Jiangsu Yida Chemical Co., Ltd., CAS: 108-65-6; Polyether-modified silicone leveling agent, manufacturer: BYK Chemical (Shanghai) Co., Ltd., CAS: 67674-67-3; Polydimethylsiloxane defoamer, manufacturer: Shenzhen Haichuan New Material Technology Co., Ltd., CAS: 9016-00-6; Hydrofluoric acid, manufacturer: Zhejiang Juhua Co., Ltd., CAS: 7664-39-3, electronic grade, 40% content; Sulfuric acid, manufacturer: Jiangyin Jianghua Microelectronics Materials Co., Ltd., CAS: 7664-93-9, electronic grade, 98% purity; Ammonium fluoride, manufacturer: Shandong Dongyue Chemical Co., Ltd., CAS: 12125-01-8, electronic grade, 99% purity; Sodium dodecylbenzenesulfonate, manufacturer: Shandong Jinghao Chemical Co., Ltd., CAS: 25155-30-0, electronic grade, 40% content; Citric acid, manufacturer: Shandong Lemon Biochemical Co., Ltd., CAS: 77-92-9, electronic grade, 99% purity; Sodium carbonate, manufacturer: Shandong Haihua Group Co., Ltd., CAS: 497-19-8; Hydrochloric acid, manufacturer: Jiangyin Jianghua Microelectronics Materials Co., Ltd., CAS: 7647-01-0, electronic grade, 37% content. Glycerin, Manufacturer: Zhejiang Jiahe Energy Chemical Co., Ltd., CAS: 56-81-5; Sodium hydroxide, manufacturer: Wanhua Chemical Group Co., Ltd., CAS: 1310-73-2; Sodium silicate, manufacturer: Shandong Dongyue Organosilicon Materials Co., Ltd., CAS: 1344-09-2; Example
[0030] This application provides an embodiment of a 2.5D glass cover AG etching process, referring to... Figure 1 This includes the following steps: S1. Use laser cutting equipment to cut the glass material according to the preset shape, and then put the cut glass into the cleaning tank for cleaning; S2. Using a screen printing machine, a composite acid-resistant ink is printed onto the entire non-AG side of the glass. The composite acid-resistant ink protective layer is printed in two stages, with each printing followed by baking and curing, ultimately forming a 30μm thick composite acid-resistant ink protective layer. The baking and curing process consists of two stages: first, a pre-baking at a low temperature of 100℃ for 15 minutes. This low-temperature pre-baking stage allows the solvent in the ink to evaporate slowly, preventing bubbles or uneven surfaces caused by rapid solvent evaporation. Then, the temperature is raised to a high temperature of 170℃ for 30 minutes for curing. This high-temperature curing allows the resin and other components in the ink to fully cross-link, forming a strong composite acid-resistant ink protective layer.
[0031] Specifically, the composite acid-resistant ink comprises the following raw materials in parts by weight: 60 parts epoxy resin, 25 parts acrylic resin, 8 parts barium sulfate, 6 parts silica, 4 parts ultrafine precipitated silica, 8 parts modified cycloaliphatic amine curing agent, 25 parts propylene glycol methyl ether acetate, 3 parts leveling agent, and 2 parts defoamer.
[0032] S3. Perform CNC machining on the glass with a composite acid-resistant ink protective layer to obtain a glass semi-finished product with a 2.5D profile; S4. Use CNC machining equipment to physically polish the edges and 2.5D curved surfaces of the glass semi-finished product. The specific steps are as follows: S41. Use a circumferential polishing machine or a top polishing machine to polish the edges of the glass semi-finished products. During polishing, the glass semi-finished products are stacked back to back in a string. S42. Use a flip polishing machine to polish the 2.5D curved surface of the glass semi-finished product.
[0033] S5. The polished glass semi-finished product is cleaned sequentially with an acidic detergent, a weakly alkaline detergent, and pure water. The acidic detergent is a 2% (w / w) mixed aqueous solution of hydrofluoric acid and citric acid. Hydrofluoric acid reacts with some metallic impurities on the glass surface, while citric acid acts as a buffer and complexing agent, selectively dissolving polishing powder, metal oxides, and surface micro-debris without causing macroscopic etching damage to the glass substrate or disrupting the interfacial bonding of the composite acid-resistant ink protective layer. The weakly alkaline detergent is a 2% (w / w) mixed aqueous solution of sodium carbonate and sodium dodecylbenzenesulfonate with a pH ≤ 12. It neutralizes residual acidic substances on the glass surface, while sodium dodecylbenzenesulfonate has excellent cleaning power, further removing oil and impurities from the glass surface.
[0034] S6. After the glass semi-finished product is hung and fixed, it is immersed in AG etching solution for etching treatment and then cleaned. Specifically, a vacuum suction cup hanger is used to adsorb one side of the composite acid-resistant ink protective layer of the glass semi-finished product for hanging and fixing. The hanger does not contact the AG etching surface of the glass semi-finished product, so as to avoid damage to the AG etching surface by the hanger and ensure the uniformity of the etching effect.
[0035] The AG etching solution includes the following raw materials in parts by weight: 30 parts hydrofluoric acid, 10 parts sulfuric acid, 12 parts ammonium fluoride, 2 parts surfactant, and 50 parts deionized water.
[0036] S7. The etched glass semi-finished product is immersed in polishing solution for chemical polishing treatment and then cleaned. The polishing solution includes the following raw materials in parts by weight: 10 parts hydrofluoric acid, 8 parts hydrochloric acid, 5 parts glycerin, and 80 parts deionized water.
[0037] S8. The glass semi-finished product is immersed in a deinking agent to remove the ink, and then washed to obtain the finished product. The deinking agent is an alkaline deinking agent composed of sodium hydroxide and sodium silicate with a mass concentration of 5%. Example
[0038] The difference between this embodiment 2 and the above embodiment 1 is that the composite acid-resistant ink in this embodiment includes the following raw materials in parts by weight: 40 parts epoxy resin, 30 parts acrylic resin, 8 parts barium sulfate, 6 parts silica, 4 parts ultrafine precipitated carbon black, 8 parts modified cycloaliphatic amine curing agent, 25 parts propylene glycol methyl ether acetate, 3 parts leveling agent and 2 parts defoamer. Example
[0039] The difference between Example 3 and Example 1 above is that the composite acid-resistant ink in this example includes the following raw materials in parts by weight: 60 parts epoxy resin, 25 parts acrylic resin, 12 parts barium sulfate, 8 parts silica, 6 parts ultrafine carbon black, 8 parts modified cycloaliphatic amine curing agent, 25 parts propylene glycol methyl ether acetate, 3 parts leveling agent and 2 parts defoamer. Example
[0040] The difference between this embodiment 4 and the above embodiment 1 is that the thickness of the composite acid-resistant ink protective layer in this embodiment is 15μm. Example
[0041] The difference between Example 5 and Example 1 above is that the weakly alkaline detergent in this example is a mixed aqueous solution of sodium carbonate and sodium dodecylbenzenesulfonate with a mass concentration of 0.5%.
[0042] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that S2 is replaced after S5 and before S6, so that the processing steps of the glass cover plate processing technology become: S1, S3, S4, S5, S2, S6, S7, S8.
[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the ultrafine silica in this example is replaced with an equal amount of silicon dioxide.
[0044] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that the silicon dioxide in this example is replaced with an equal amount of barium sulfate.
[0045] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that barium sulfate in this example is replaced with an equal amount of ultrafine silica.
[0046] Comparative Example 5 The difference between Comparative Example 5 and Example 3 is that the weakly alkaline detergent in this example is a mixed aqueous solution of sodium carbonate and sodium dodecylbenzenesulfonate with a mass concentration of 5%.
[0047] The finished glass covers prepared in Examples 1-5 and Comparative Examples 1-5 were used as test samples. Tests were conducted on each group of samples to examine the peel retention rate of the composite acid-resistant ink protective layer before and after high temperature, the roughness of the AG surface, and the uniformity of the gloss of the non-AG surface. The test results are shown in Table 1.
[0048] From the samples prepared in mass production of Examples 1-5 and Comparative Examples 1-5, 100 samples were selected from each group and divided into two groups of 50 pieces each. The peel retention rate of the composite acid-resistant ink protective layer before and after high temperature was tested. I. Initial peel force test before high temperature Take 50 samples that have just finished curing, and gently wipe the ink surface with a lint-free cloth dipped in anhydrous ethanol to remove dust and impurities; Use a blade to pre-make a complete peeling opening with a width of 5mm at the edge of the ink layer on each sample, ensuring that the ink is completely separated from the glass at the opening; The sample is fixed horizontally on the test platform of the 90° peel force tester, the clamp holds the pre-made opening edge of the ink layer, and the peel speed is set to 30mm / min; Three different test points were selected for each sample, and the average force value during the peeling process was recorded. Abnormal data indicating ink cohesive fracture were discarded. The average peel force of 50 samples was calculated and denoted as the initial peel force F0. II. High-Temperature Environment Simulation Treatment 1. Place the 50 sample pieces that have completed the initial test, together with the remaining 50 untested parallel samples, into a forced-air drying oven with a preset temperature of 190℃. 2. Maintain constant temperature for 30 minutes to completely simulate the extreme high temperature conditions of ink before CNC processing and etching. After the process, allow it to cool naturally to 25°C and let it stand for 30 minutes. 3. Observe the ink surface of all samples with a metallographic microscope. After confirming that there is no softening, stickiness, shrinkage, peeling, cracking and peeling, proceed to the next step of testing.
[0049] III. Residual peel force test after high temperature 1. Repeat the above peel force test operation for 100 samples after high temperature treatment. For each sample, select 3 different points for testing and record the average peel force. 2. Discard any outliers such as complete ink layer detachment or significant deviations in test data. Calculate the average peel force of all valid samples, denoted as the high-temperature peel force F1. IV. Calculation of Peel Force Retention Rate The final result is calculated using the formula: High-temperature peel force retention rate = F1 / F0 * 100% Valid test data must meet the requirement that the relative deviation between parallel samples is ≤5% to ensure the repeatability and reliability of the results.
[0050] A high-temperature peel force retention rate > 85% is considered excellent; a high-temperature peel force retention rate ≥ 75% is considered acceptable; and a high-temperature peel force retention rate < 75% is considered unacceptable.
[0051] AG surface roughness uniformity test: 2.5D glass covers that meet customer processing requirements were selected as the baseline sample control group. 100 samples were selected from the samples prepared in mass production of Examples 1-5 and Comparative Examples 1-5.
[0052] Five different test points were selected for each sample. Non-contact testing was performed using a white-light interferometric three-dimensional optical profilometer equipped with an electric displacement stage to obtain the surface roughness Sa at each point. The average roughness of the five points on the same sample was calculated. Using the average roughness of the control group as a reference, a roughness mean deviation ≤ ±0.03 μm was considered acceptable for a single piece, while an absolute deviation > ±0.03 μm was considered unacceptable. The number of unacceptable samples in each group was counted, and the failure rate was calculated as: number of unacceptable samples / 100. If the number of unacceptable samples ≤ 1 (failure rate ≤ 1%), the group was considered acceptable; if the number of unacceptable samples > 1 (failure rate > 1%), the group was considered unacceptable. Non-AG surface gloss uniformity test: 2.5D glass covers that meet customer processing requirements were selected as the baseline sample control group. 100 samples were selected from the samples prepared in mass production of Examples 1-5 and Comparative Examples 1-5.
[0053] Select 5 different test points on each sample, use a 60° gloss meter to test the gloss values of the 5 different test points on the non-AG surface area of the glass cover plate, and calculate the average gloss value of the five points for the same sample; taking the gloss value of the reference sample control group as the reference, a single piece is judged as qualified if the absolute gloss deviation is ≤±0.03GU, and a single piece is judged as unqualified if the absolute gloss deviation is >±0.03GU. Count the number of unqualified samples in each group, and calculate the unqualified rate = number of unqualified samples / 100; if the number of unqualified samples is ≤1 (unqualified rate ≤1%), the group is judged as qualified; if the number of unqualified samples is >1 (unqualified rate >1%), the group is judged as unqualified.
[0054] Table 1 Experimental data of Examples 1-5 and Comparative Examples 1-5
[0055] The analysis results are as follows: In Examples 1-3, barium sulfate, silica and ultrafine white carbon black are synergistically compounded according to particle size gradation, the micro-porosity after ink film formation is extremely low, the adhesion between the resin and the glass interface after high-temperature crosslinking is extremely strong, and the final high-temperature peel force retention rates are all >85% reaching the excellent grade, the ink layer has no adhesion attenuation at a high temperature of 190°C, and there is no erosion risk in the whole process. In contrast, in Comparative Examples 2-4, any one filler is replaced by another filler in equal amount respectively, which breaks the gradation filling effect of three-level particle sizes, resulting in micro-pores after the ink film is formed, and local defects appear in the resin crosslinking network at high temperature. The final high-temperature peel force retention rates are all <75% and judged as unqualified. During the etching process, hydrofluoric acid penetrates from the pores into the interface between the ink and the glass, causing the non-AG surface to be slightly etched and fogged, and the gloss uniformity of all non-AG surfaces is unqualified.
[0056] In Example 1, the screen printing ink process is arranged before the CNC machining, the non-AG surface of the glass is completely covered and protected by the ink from the mechanical machining stage, so it will not be scratched by polishing powder or corroded by acid-base detergent throughout the whole process. Finally, the AG surface roughness uniformity and the non-AG surface gloss uniformity are all qualified, and the mass production unqualified rate is ≤1%. In contrast, in Comparative Example 1, the screen printing ink process is moved to after the completion of all CNC machining and polishing. The non-AG surface of the glass has no protection during the whole mechanical machining process, a large amount of polishing powder is embedded in the micro-scratches on the glass surface during the edge polishing process, which cannot be completely removed by subsequent cleaning. Finally, the AG surface roughness uniformity and the non-AG surface gloss uniformity are all unqualified.
[0057] In Example 1, a weak alkaline detergent with a standard concentration of 2% is used, which can not only completely neutralize the residual acid liquid and remove surface oil stains, but also will not erode the ink layer, and both uniformity indicators are qualified. In Example 5, a low-concentration weak alkaline detergent of 0.5% is used, which has no risk of eroding the ink due to excessive alkalinity, and only has slightly limited decontamination ability in extreme oil stain scenarios, with the overall performance still qualified.
[0058] In contrast, Comparative Example 5 used a 5% high-concentration weak alkaline detergent. The excessive OH⁻ ions slowly penetrated into the ink surface, damaging the interfacial bond between the ink and the glass. After deinking, the non-AG surface showed microscopic haziness, and ultimately the gloss uniformity of the non-AG surface failed to meet the requirements.
[0059] In summary, this application, through a composite acid-resistant ink system consisting of epoxy resin, acrylic resin matrix, barium sulfate, silica, and ultrafine silica, combined with a process logic of "print protection first, then CNC machining," ultimately achieved a basic qualification line of ink high-temperature peel strength retention rate ≥75%. The mass production yield of AG surface roughness uniformity and non-AG surface gloss uniformity was stably controlled above 99%, and the overall performance was significantly better than all comparative solutions.
[0060] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A 2.5D glass cover plate AG etching process, characterized in that, The steps are as follows: S1: Cleaning is performed after laser cutting of the glass raw material; S2: Print composite acid-resistant ink on the non-AG side of the glass, and form a composite acid-resistant ink protective layer after baking and curing. S3: CNC machining is performed on the glass printed with a composite acid-resistant ink protective layer to obtain a glass semi-finished product with a 2.5D profile; S4: Physically polish the edges and 2.5D curved surfaces of the glass semi-finished product; S5: The polished glass semi-finished product is cleaned in sequence with acidic detergent, weak alkaline detergent and pure water; S6: After the glass semi-finished product is hung and fixed, it is immersed in AG etching solution for etching treatment and then cleaned. S7: The etched glass semi-finished product is immersed in polishing liquid for chemical polishing treatment and then cleaned. S8: Immerse the glass semi-finished product in a deinking agent to remove the ink, and then clean it to obtain the finished product.
2. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The composite acid-resistant ink comprises the following raw materials in parts by weight: 40-60 parts epoxy resin, 20-30 parts acrylic resin, 8-12 parts barium sulfate, 4-8 parts silica, 3-6 parts ultrafine carbon black, 5-10 parts modified cycloaliphatic amine curing agent, 15-25 parts propylene glycol methyl ether acetate, 1-3 parts leveling agent, and 1-3 parts defoamer.
3. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The thickness of the composite acid-resistant ink protective layer is 15-30 μm.
4. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The composite acid-resistant ink protective layer described in step S2 is printed twice, and each time it is baked and cured. The baking and curing parameters are as follows: first, pre-bake at a low temperature of 80℃-100℃ for 15-20 minutes, and then heat up to a high temperature of 150-170℃ for 30-40 minutes.
5. The 2.5D glass cover AG etching process according to claim 1, characterized in that, In S6, a vacuum suction cup hanger is used to attach and fix the composite acid-resistant ink protective layer of the glass semi-finished product to one side, without the hanger contacting the AG etched surface of the glass semi-finished product.
6. The 2.5D glass cover AG etching process according to claim 1, characterized in that, Step S4 includes the following steps in sequence: S41: Use a circumferential polishing machine or a top polishing machine to polish the edges of the glass semi-finished products. During polishing, the glass semi-finished products are stacked back to back in a string. S42: Use a flip polishing machine to polish the 2.5D curved surface of the glass semi-finished product.
7. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The acidic detergent in step S5 is a mixed aqueous solution of hydrofluoric acid and citric acid with a mass concentration of 2-5%; the weakly alkaline detergent is a mixed aqueous solution of sodium carbonate and sodium dodecylbenzenesulfonate with a mass concentration of 0.5-2%.
8. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The AG etching solution comprises the following raw materials in parts by weight: 20-30 parts hydrofluoric acid, 10-15 parts sulfuric acid, 8-12 parts ammonium fluoride, 0.5-2 parts surfactant, and 40-50 parts deionized water.
9. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The polishing solution comprises the following raw materials in parts by weight: 10-15 parts hydrofluoric acid, 5-8 parts hydrochloric acid, 3-5 parts glycerin, and 70-80 parts deionized water.
10. The 2.5D glass cover AG etching process according to claim 1, characterized in that, The deinking agent is an alkaline deinking agent composed of sodium hydroxide and sodium silicate at a mass concentration of 5-8%.